The Value of a Green Card in the U.S. Marriage Market: A Tale of Chain Migration? - Cynthia Bansak; Eva Dziadula; Madeline Zavodny (Institute of Labor Economics (IZA), 2023)
This study examines the impact of having a clear path to lawful permanent resident status, or a "green card," and naturalized citizenship on marital status and spousal characteristics among Chinese immigrants in the United States. A series of U.S. policy changes in the early 1990s made all mainland Chinese immigrants already present in the country eligible for a green card. We examine the effect of those policy changes on Chinese immigrants' marriage market outcomes relative to other East Asian immigrants. Using 1990 and 2000 U.S. Census data, we find that the share of Chinese immigrants who are married increased after they became automatically eligible for a green card. In particular, highly educated Chinese immigrants became relatively more likely to be married with a spouse living with them and relatively less likely to be married with a spouse living elsewhere. This pattern suggests that some Chinese spouses immigrated after their husband or wife received legal status, or spousal chain migration occurred. We also find that highly educated Chinese immigrants benefited in the marriage market in terms of spousal education and earnings, but less-educated Chinese immigrants did not. Meanwhile, less-educated Chinese-born women became relatively more likely to marry a U.S. native.
Keywords: J12; J15; K37; 330; immigration; marriage markets; assortative matching; legal status; China